2008
DOI: 10.1002/srin.200806139
|View full text |Cite
|
Sign up to set email alerts
|

A Furnace Control System for Tracing Reference Reheating Curves

Abstract: A control system for tracing the reference reheating curves of individual steel slabs in continuous furnaces is presented. The system enables the predefined, controllable reheating of slabs in a furnace. The slab temperatures are obtained by the simulation of a mathematical model of the slab‐reheating process. The interior of the continuous furnace is divided into six control zones. The individual zone temperatures are adjusted by the control system in such a way that the temperatures of the slabs in the zone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
5
0
3
Order By: Relevance
“…In the last decade, new solving schemes as a genetic algorithm, the inverse method to solve Fourier's Differential Equation, and the control system for tracing reference reheating curves were published in steel research international.…”
Section: Heat and Mass Transfermentioning
confidence: 99%
“…In the last decade, new solving schemes as a genetic algorithm, the inverse method to solve Fourier's Differential Equation, and the control system for tracing reference reheating curves were published in steel research international.…”
Section: Heat and Mass Transfermentioning
confidence: 99%
“…Aus diesem Grund wird hier ein fü r die Regelungsaufgabe maßgeschneidertes vereinfachtes mathematisches Modell entwickelt, das die Ofentemperaturen als Eingangsgrö ßen verwendet und deren unabhä ngige Einstellbarkeit voraussetzt. Das Modell wurde erstmals in Steinboeck et al (2010) vorgeschlagen und basiert auf Vereinfachungen, die jenen von Hollander, Zuurbier (1982); Pedersen, Wittenmark (1998); Rixin, Baolin (1992); Sibarani, Samyudia (2004); Staalman (2004); Vode et al (2008) ä hnlich sind. Das Modell wurde mithilfe von einzelnen instrumentierten Testbrammen, welche mit Thermoelementen die sonst nicht messbare Brammentemperatur aufzeichnen, validiert.…”
Section: Mathematisches Modellunclassified
“…Zumeist kommen hierbei PI-oder PID-Regler zum Einsatz (vgl. Dahm, Klima, 2002;Ditzhuijzen et al, 2002;Doss et al, 1992;Hollander, Zuurbier, 1982;Icev et al, 2004;Nederkoorn et al, 2011;Staalman, 2004;Vode et al, 2008;Zhang et al, 2002). Die zu regelnden Zonentemperaturen T Ç z ðtÞ werden an diskreten Stellen im Ofen mit Thermoelementen gemessen.…”
Section: Mathematisches Modellunclassified
See 1 more Smart Citation
“…However, these open-loop approaches may be inadequate if the plant exhibits significant uncertainties. Dahm and Klima (2002); Doss et al (1992); Ezure et al (1997); Facco et al (1990); Honner et al (2001); Knoop and Moreno Pérez (1994); Leden (1986); Marino et al (2004); Pedersen and Wittenmark (1998); Shenvar (1994); Staalman (2004); Vode et al (2008); Wang et al (2004); Westdorp (1988); Yoshitani et al (1994) reported on feedback control for slab temperatures, which is usually realized as a cascade control scheme. Especially for non-steady state operating conditions, trajectory tracking control may be required.…”
Section: Existing Furnace Control Schemesmentioning
confidence: 99%